Solvatochromism and Prototropism of Some Alkyl Substituted Phenols - Kalai Selvi, D.; Sundari, V. (Asian Journal of Chemistry, 2010)
The effects of solvents on absorption and flurescence of somedimethyl substituted phenols (DMPS) and trimethyl phenols(TMPS) show that hydrogen bonding interactions are predominant.The site of hydrogen donor interaction of water with DMPS andTMPS in the excited singlet state is found to be differnt from thesite of interaction in the ground state. Acidity constants for neutralmonoanionequilibria in So and S1 states have been determined anddiscussed.